Health Education in preventing stunting and utilizing family medicinal plants in Gebang Ilir Village - Sulistiorini Indriaty; Muhamad Agustian Erlangga; Atiqoh Rohmawati; Vinie Regina Putri Gianto; Dian Dwi Septiani; Nafa Trisnia; Hilal Haidar; Saeful Ghozi; Muhammad Kusnendar; Nahla Nur Amaliyah; Grendy Rezaldi Arianto (Universitas Muhammadiyah Magelang, 2023)
Gebang Ilir Village is one of the villages in the Gebang District, situated on the northern coast of Java. The community faces several issues, including high stunting rates and a lack of understanding about the usage of family medicinal plants. The method employed in this program involves socialization through presentations and training. As a result of these activities, the community now has a better understanding of stunting and its prevention, as well as knowledge about family medicinal plants and their proper usage. Additionally, our partners have enhanced their skills in using emprit ginger and cardamom to create instant granules.